The Usefulness of Intrapartum Transperineal Ultrasonography for the Prediction of Mode of Delivery - Erdinc Saridogan; Ozlem Moraloglu Tekin (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: We aimed to assess the accuracy of intrapartum transperineal ultrasonography that is non-invasive, easy to learn, rapid to perform, comfortable for pregnant women, and low-cost method to evaluate the progress of labor objectively.